Persepsi Mahasiswa Terhadap E-commerce melalui Facebook di: Kecamatan Sumbersari Kabupaten Jember - Senna Saflianda Cendikia Putra; Ketut Indraningrat; Abdul Halim (UPT Penerbitan Universitas Jember, 2017)
This study aimed to describe the students’ perceptions of E-commerce via Facebook in the subdistrict Sumbersaridistrict of Jember. Research approach used in this study is a qualitative research, study subjects are set in a waythat amounted to 7 Sampling Snowball informants students. Informants were selected based on experience using theE-commerce via Facebook and advised his colleagues who had similar experiences to serve as the next informant.The method used is Triangulation of data, whereas the method of analysis using descriptive analysis aims todetermine the depiction of the condition of the research is based on interviews of informants answer. The datacollection process begins with interviews and retrieval of documents directly to the informant. The results showedabout their perceptions of E-commerce via Facebook divided into two groups, namely that the E-commerce viaFacebook is a trend to shop online nowadays, and is considered very good, effective and efficient. Also obtainedinformation that the majority of informants using E-commerce via Facebook on its own initiative and rest on therecommendation of a friend.